Maintaining the rated level of power supply reliability under the condition of distributed generation implementation - Банузаде, Сахрагард Саид; Попов, Владимир Андреевич; Ткаченко, Вадим Владиславович; Журавлев, Андрей Александрович; Шпак, Денис Владимирович (Eastern-European Journal of Enterprise Technologies, 2016)
In order to minimize costs of power supply companies and potential investors, the study related to the formation of a strategy to ensure the rated level of power supply reliability in conditions of integration of distributed generation sources into electrical networks is carried out in the paper. The possibility of the logframe use to evaluate the integrated reliability indicators in the conditions of equipment of electrical networks with modern switching devices and presence of generating sources under different settings and locations is shown. The experimental computations reveal that only a coordinated solution of the problems of electrical network partitioning in terms of reliability optimization and implementation of technical specifications to enable their "island" mode at the occurrence of distributed generation sources makes it possible to make the most cost-effective decisions. The results can be directly used in the practical work of operational units and prospective development departments of energy supply companies, serve as an important component in the multicriteria evaluation of application options of distributed generation.